2010
DOI: 10.1136/ard.2009.117580
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 regulates leucocyte behaviour in fibrotic lung disease

Abstract: Objectives-Reduced caveolin-1 levels in scleroderma lung fibroblasts and the lungs of bleomycin-treated mice promote collagen overexpression and lung fibrosis. We now evaluate whether caveolin-1 is deficient in leucocytes from bleomycin-treated mice and scleroderma patients and examine the consequences of this deficiency and its reversal.Methods-Mice or cells received the caveolin-1 scaffolding domain (CSD) peptide to reverse the pathological effects of reduced caveolin-1 expression. In bleomycin-treated mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(114 citation statements)
references
References 30 publications
5
109
0
Order By: Relevance
“…Wang et al (111) and Tourkina et al (102) reported marked reduction in cav-1 expression in lung tissues or monocytes/neutrophils from patients with idiopathic pulmonary fibrosis or scleroderma, respectively, compared with controls (102,103,111). Moreover, Tourkina et al demonstrated the potential role of cav-1 as a lung-protective protein by using the cav-1 CSD peptide to treat scleroderma/fibrosis (102,103,111).…”
Section: Evidence For a Role Of Cav-1 In Pmn-mediated Inflamma-mentioning
confidence: 91%
“…Wang et al (111) and Tourkina et al (102) reported marked reduction in cav-1 expression in lung tissues or monocytes/neutrophils from patients with idiopathic pulmonary fibrosis or scleroderma, respectively, compared with controls (102,103,111). Moreover, Tourkina et al demonstrated the potential role of cav-1 as a lung-protective protein by using the cav-1 CSD peptide to treat scleroderma/fibrosis (102,103,111).…”
Section: Evidence For a Role Of Cav-1 In Pmn-mediated Inflamma-mentioning
confidence: 91%
“…Ten-week-old, male CD1 mice (Charles River Laboratories, Boston, MA) maintained under pathogen-free conditions were treated with bleomycin (Teva Parenteral Medicines, Irvine, CA) by the "direct model" as previously described (26) or the "pump model." In the pump model, osmotic minipumps (ALZET 1007D; DURECT, Cupertino, CA) containing either 100 l saline vehicle or bleomycin (100 U/kg) designed to deliver their contents at 0.5 l/h for 7 days were implanted under isofluorane anesthesia under the loose skin on the back of the mice slightly posterior to the scapulae.…”
Section: Bleomycin Treatment Of Mice and Harvesting Of Tissuementioning
confidence: 99%
“…It has previously been reported that the expression of CAV1 is decreased in tissues and peripheral blood mononuclear cells of patients with SSc 11 12 22. In addition, CAV1 knockout mice develop progressive tissue fibrosis resembling that found in human SSc 9 11 23.…”
Section: Discussionmentioning
confidence: 90%
“…Numerous studies published during the past decade have provided strong evidence that CAV1 participates in the pathogenesis of fibrotic diseases through regulation of TGFβ receptor internalisation and degradation, effectively decreasing or abolishing TGFβ signalling with a resultant antifibrotic effect 9. Indeed, a reduction in CAV1 expression has been reported in affected skin, lungs and peripheral blood cells of patients with SSc, and CAV1-deficient mice spontaneously develop progressive tissue fibrosis 11 12. Moreover, decreased expression of CAV1 has also been reported in other human fibrotic disorders 13 14…”
mentioning
confidence: 99%